2018
DOI: 10.1021/acs.cgd.8b00240
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polymer Crystallizability on the Formation of Polymer-Urea-Inclusion Compounds

Abstract: Polymer-urea inclusion compounds (P-U-ICs) were formed using a series of linear aliphatic polyesters with varying crystallizabilities: from highly crystalline to wholly amorphous. The traditional hexagonal P-U-ICs were obtained irrespective of the crystallinities of the neat guest polyesters. Two distinct co-crystallization mechanisms were evident based on the observation of the change in thermal stabilities of the ICs using DSC and the crystal morphologies by SEM; one involves polymer chain folding back and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The feature bands of PCL and urea are shown in the spectra of all IC samples. The N–H stretching bands of pure urea at 3428 and 3333 cm –1 shifted to lower wavenumbers, indicating the formation of the hexagonal urea crystal structure in ICs. ,, …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The feature bands of PCL and urea are shown in the spectra of all IC samples. The N–H stretching bands of pure urea at 3428 and 3333 cm –1 shifted to lower wavenumbers, indicating the formation of the hexagonal urea crystal structure in ICs. ,, …”
Section: Resultsmentioning
confidence: 91%
“…The N−H stretching bands of pure urea at 3428 and 3333 cm −1 shifted to lower wavenumbers, indicating the formation of the hexagonal urea crystal structure in ICs. 24,28,43 In the spectrum of pure PCL, the blue shift of the carbonyl band normally indicates a conversion from crystalline phases to amorphous phases. 24,44 The guest PCL can be considered as an amorphous state when isolated and separately included in a host canal, according to a previous report.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An IC with canal-shape compact structure typically leads to a higher melting temperature than the neat host crystal. [10,11,15] However, when the host structure is non-canal, such as a layered structure, the complex is normally metastable with loose packing and lower melting temperatures. For example, the reported layered PEO-TU complexes had lower melting temperatures than neat TU.…”
Section: Structures Of Pmtd and Pstdmentioning
confidence: 99%
“…[8][9][10] Polymer chains are isolated in the nanoscale canals formed by small molecular hosts and adopt extended states. [11][12][13][14] More interestingly, it has been reported that the extended chain conformations of guest polymer chains can be largely retained after removing the host molecules. [13,[15][16][17] Distinct to most methods, including stretching, rubbing, or chemical reactioncontrolled methods, like topochemical polymerizations, which are mainly applicable to semicrystallize polymers, forming ICs is a "bottom-up" approach to control chain alignment of polymeric materials regardless of polymer crystallization capacity.…”
mentioning
confidence: 99%